2018
DOI: 10.1055/a-0732-5060
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of duodenal bulb biopsy for diagnosis of celiac disease: a systematic review and meta-analysis

Abstract: Background and study aims  Although duodenal biopsy is considered the “gold standard” for diagnosis of celiac disease, the optimal location of biopsy within the small bowel for diagnosis remains unclear. The primary aim of this study was to perform a structured systematic review and meta-analysis to evaluate the diagnostic utility of endoscopic duodenal bulb biopsy for celiac disease. Patients and methods  Searches of PubMed, EMBASE, Web of Science, and Cochrane Library databases were performed from 2000 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 53 publications
0
25
0
2
Order By: Relevance
“…Female preponderance in our study (73%) is comparable with this as well as other international studies. [19] Extensive literature review and meta-analysis performed by McCarty et al [20] revealed that duodenal bulb biopsy increases the diagnostic yield by 5% and 4% in adults and children, respectively. In our study, although there was no strict criteria for duodenal bulb biopsy, but overall 9.3% (n = 13) of patients with CD were diagnosed on biopsy alone, with TTG IgA level <20 units.…”
Section: Discussionmentioning
confidence: 99%
“…Female preponderance in our study (73%) is comparable with this as well as other international studies. [19] Extensive literature review and meta-analysis performed by McCarty et al [20] revealed that duodenal bulb biopsy increases the diagnostic yield by 5% and 4% in adults and children, respectively. In our study, although there was no strict criteria for duodenal bulb biopsy, but overall 9.3% (n = 13) of patients with CD were diagnosed on biopsy alone, with TTG IgA level <20 units.…”
Section: Discussionmentioning
confidence: 99%
“…Three biopsy samples per patient were taken from the distal duodenum. Duodenal ampulla biopsies were routinely obtained since 2010 because the latest studies have suggested that that region may be the only region affected by CD [8].…”
Section: Endoscopic Evaluationmentioning
confidence: 99%
“…An antibody test followed by a small intestinal biopsy evaluation is the gold standard for the definitive diagnosis of CD [36,39]. Adequate small intestinal sampling is essential in this regard and studies have concluded that at least one biopsy from the duodenal bulb and at least four biopsies from the distal duodenum are needed for an accurate diagnosis [40,41]. Biopsy appearances in keeping with CD include scalloping, villous flattening, and fissuring of mucosal folds.…”
Section: Celiac Disease (Cd)mentioning
confidence: 99%
“…Biopsy appearances in keeping with CD include scalloping, villous flattening, and fissuring of mucosal folds. Small intestinal appearances can become more pronounced with disease progression [17,40,41]. According to the Marsh classification, the intestinal biopsy changes are classified on the extent of increased intraepithelial lymphocytes, crypt hyperplasia, and villous atrophy [42].…”
Section: Celiac Disease (Cd)mentioning
confidence: 99%